The effects of less-expensive plant protein sources replaced with soybean meal in the juvenile diet of grass carp (Ctenopharyngodon idella): growth, nutrient utilization and body composition - Koprucu, Kenan; Sertel, Ebru (Springer, 2012)
In this study, the effects of less-expensive protein sources replaced with soybean meal on growth performance, nutrient utilization and body composition of juvenile grass carp were investigated. For this purpose, a control diet containing 42% soybean meal was prepared. Cotton seed meal (CSM), sunflower meal (SFM) and corn meal (CM) were added to the experimental diets by replacing 100% of the soybean meal protein used in the control diet. All diets were iso-nitrogenous (40% crude protein) and iso-caloric (19.5 MJ kg(-1) gross energy). Each treatment had three replicates, and 20 juvenile grass carps (3.5 +/- A 0.1 g, initial weight) were located in per replicate. The fish were fed to satiety three times in a day during 3 months at 26A degrees C of water temperature in glass aquarium (45 l). The results of the study showed that the weight gain (308.6-448.6%), specific growth rate (1.56-1.89%/day), feed conversion rate (1.2-1.9), protein efficiency ratio (1.32-2.08), and apparent digestibility coefficients of protein (80.5-89%) or sum of amino acids (80.5-88.9%) were not significantly affected by the experimental diets, except diet CM. All of these values obtained for the diet CM were significantly lower than those of fish fed on the control, CSM and SFM diets. However, there were no significant differences between the lipid digestibility of the diets, and crude protein, lipid, and gross energy contents in the whole body of fish in experiments. In conclusion, CSM and SFM diets were highly utilized by juvenile grass carp, but not CM diet. These results combined with the remarkable acceptability of diets containing high levels of plant protein ingredients with identical growth performances of juvenile grass carp show clearly that dietary soybean meal level can be considerably reduced without any adverse consequence in terms of somatic growth and nitrogen utilization.
Keywords: Digestibility; Grass carp; Growth; Nutrient utilization; Plant proteins